2022
DOI: 10.1111/inm.13033
|View full text |Cite
|
Sign up to set email alerts
|

The path of depression among frontline nurses duringCOVID‐19 pandemic: A fuzzy‐set qualitative comparative analysis

Abstract: This study aimed to explore the combination of different conditional variables that led to depressive symptoms among frontline nurses who were fought against COVID‐19 during the outbreak in Wuhan City, Hubei Province of China. The study was conducted in August 2020, which included 331 frontline clinical nurses who supported Wuhan's fight against COVID‐19. The age range was 21–57 years and included 315 female nurses and 16 male nurses. This study used the fuzzy‐set qualitative comparative analysis research meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…One way to aid doctors in diagnosing depression is through a decision support system driven by neuro-fuzzy. In 2022 Liang et al [34] used fuzzy qualitative comparative review to disclose the complex trajectory that contribute to depression in front-line nurses throughout the COVID-19 pandemic.…”
Section: Related Workmentioning
confidence: 99%
“…One way to aid doctors in diagnosing depression is through a decision support system driven by neuro-fuzzy. In 2022 Liang et al [34] used fuzzy qualitative comparative review to disclose the complex trajectory that contribute to depression in front-line nurses throughout the COVID-19 pandemic.…”
Section: Related Workmentioning
confidence: 99%
“…Different authors have observed a high prevalence of anxiety and depression in HCPs [24][25][26][27] . Furthermore, the presence of these psychological symptoms may, in turn, increase the risk of developing BOS 27 BOS does not only show impact on the personal or professional spheres but can, furthermore, increase the risk of developing physical symptoms, as pain in the upper limb, and in the cervical and/or lumbar vertebral regions 31 . The type of pain developed corresponds to unspeci c pain becoming a worldwide health problem due to its impact and prevalence.…”
Section: Burnout Syndrome Among Healthcare Professionalsmentioning
confidence: 99%
“…Among the various types of QCA, fuzzy set qualitative comparative analysis (fsQCA) uses the fuzzy set scale, which is more applicable to variables with multiple categorical and continuous variables. It avoids classifying study cases as "fully in" or "fully out" and has a broader range of applications [ 35 ]. Therefore, the main aim of this study is to provide a theoretical basis for the proposal of related policies by exploring the different configurations that contribute to the TI of primary public health workers and the role of each influencing factor in the configurations using the regression model and fsQCA.…”
Section: Introductionmentioning
confidence: 99%